Enhancing Mathematical Problem-Solving Skills of Indonesian Junior High School Students through Problem-Based Learning: a Systematic Review and Meta-Analysis - Suparman, Suparman; Yohannes, Yohannes; Arifin, Nur (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
Many researchers have conducted previous meta-analysis studies regarding problem-based learning (PBL) to enhance problem-solving skills. However, their research does not focus on mathematical problem-solving skills (MPSS). This study aims to summarize, estimate, and evaluate PBL implementation's effect in enhancing the MPSS of Indonesian junior high school (JHS) students and investigate the study characteristics that affect the heterogeneous effect size data. Twenty-nine relevant primary studies published in national and international journals and proceedings during 2011 – 2020 were analyzed using the systematic review and meta-analysis. The analysis tool used the Comprehensive Meta-Analysis (CMA) software by selecting the formula of Hedge to determine its effect size. The result showed that the overall PBL implementation had a medium positive effect (g = 0,743; p less than 0,05), significantly enhancing the MPSS of Indonesian JHS students based on the random effect model. Also, the characteristics of sample size, research area, sampling technique, and publication year did not affect the heterogeneous effect size data. These results suggest that Indonesian JHS mathematics teachers should select PBL as one of the best solutions in implementing mathematics learning in the classroom to enhance students' MPSS.